BIOCHEMICAL ANALYSIS OF AN ENDEMIC FRESHWATER CRAB, SARTORIANA SPINIGERA (WOOD-MASON, 1871) FROM EAST COAST OF INDIA - P. K. PATI,; B. C. GURU,; P. ROUTRAY, (The Bioscan, 2020)
In the present investigation an attempt has been made to know the biochemical composition of freshwater crab meat of Sartoriana spinigera (Wood-Mason, 1871) before and after their spawning seasons during the months of January to March and July to September. The protein content of meat of female crabs varied from 30.03% to 59.29%, lipid 7.01% to 11.29% and ash between 38.75 and 39.44% dry weight, whereas the moisture ranged between 71.26% and 79.51%. The protein, lipid and ash contents were recorded highest during the month of January to March whereas, lowest percentages of these were observed during July to September. The biochemical composition of crab meat having high protein justifies the edible quality of these crabs by humans.